2022
DOI: 10.3897/phytokeys.205.85866
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of 997 nuclear genes reveals the need for extensive generic re-delimitation in Caesalpinioideae (Leguminosae)

Abstract: Subfamily Caesalpinioideae with ca. 4,600 species in 152 genera is the second-largest subfamily of legumes (Leguminosae) and forms an ecologically and economically important group of trees, shrubs and lianas with a pantropical distribution. Despite major advances in the last few decades towards aligning genera with clades across Caesalpinioideae, generic delimitation remains in a state of considerable flux, especially across the mimosoid clade. We test the monophyly of genera across Caesalpinioideae via phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
277
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(297 citation statements)
references
References 133 publications
17
277
2
1
Order By: Relevance
“…Additionally, Brenan (1966Brenan ( , 1986 noted that the epicarp of Adenopodia pods remains attached to the endocarp, whereas these structures separate in the mature pods of Entada. In their review of the genera of tribe Mimoseae, Lewis and Elias (1981) used this suite of characters to argue for a more parsimonious placement of Adenopodia within the informal Piptadenia group of genera. This placement of Adenopodia, separate from Entada in the Piptadenia-containing Mimosa clade (sensu Koenen et al 2020), is supported by recent large-scale phylogenomic analyses (Koenen et al 2020;Ringelberg et al 2022). In that same review of Mimoseae genera, Lewis and Elias (1981) highlighted the close affinity between Entada and Elephantorrhiza Benth., an essentially southern African genus of eight species of geoxylic suffrutices, shrubs or small trees and placed them in their informal Entada group.…”
Section: Generic Delimitationmentioning
confidence: 77%
“…Additionally, Brenan (1966Brenan ( , 1986 noted that the epicarp of Adenopodia pods remains attached to the endocarp, whereas these structures separate in the mature pods of Entada. In their review of the genera of tribe Mimoseae, Lewis and Elias (1981) used this suite of characters to argue for a more parsimonious placement of Adenopodia within the informal Piptadenia group of genera. This placement of Adenopodia, separate from Entada in the Piptadenia-containing Mimosa clade (sensu Koenen et al 2020), is supported by recent large-scale phylogenomic analyses (Koenen et al 2020;Ringelberg et al 2022). In that same review of Mimoseae genera, Lewis and Elias (1981) highlighted the close affinity between Entada and Elephantorrhiza Benth., an essentially southern African genus of eight species of geoxylic suffrutices, shrubs or small trees and placed them in their informal Entada group.…”
Section: Generic Delimitationmentioning
confidence: 77%
“…The Stryphnodendron and Mimosa clades, taxa from which were used to root trees in this study, are highlighted in orange and purple, respectively and indicated with an asterisk. phylogenetic and phylogenomic analyses until recently (Brown et al 2022;Ringelberg et al 2022). Recent efforts to resolve phylogenetic relationships within the species-rich Archidendron clade have been hampered by a paucity of molecular data or incomplete taxon sampling in previous studies (Brown et al 2008;Brown et al 2011;Koenen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We show that sect. Arthrosamanea, with expanded taxon sampling relative to Koenen et al (2020), and as also shown by the study of Ringelberg et al (2022), is monophyletic with only two exceptions: Albizia leonardii Barneby & J.W. Grimes which is placed among taxa of the 'senegalioid grade' (Ringelberg et al 2022;Terra et al 2022) and Albizia carbonaria Britton that is more closely related to Pseudosamanea (Koenen 2022b;Ringelberg et al 2022).…”
Section: Discussionmentioning
confidence: 67%
“…Finally, neither Zygia P. Browne nor Marmaroxylon Killip are monophyletic, although a new generic classification for those genera has yet to be proposed (Ferm et al 2019). The non-monophyly of Albizia documented here and elsewhere (Koenen et al 2020;Ringelberg et al 2022) is thus not a surprise and reflects the state of flux surrounding generic delimitation in mimosoids, especially within the ingoid clade. Some of the taxonomic proposals of Barneby and Grimes (1996) relative to the American segregates of Albizia s.l.…”
Section: Discussionmentioning
confidence: 68%